MAY 4 BCIA BOARD MEETING - HAMILTON J (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Tobacco Institute memo regarding Business Council on Indoor Air (BCIA) May 4, 1993 board meeting. Lists attendees. Discusses inddor air quality legislation and the lethal carpeting issue. Describes plan to write a paper on source management. Explores research into problems with ventilation rates.